Tanggung jawab Sosial Korporasi dan Hak-Hak Masyarakat Hukum Adat - Afrizal, - (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2013)
This article scrutinizes the implementation of Corporate Social Responsibility (CSR) concept on the recognition of indigenous societyâs rights over agrarian resources. It is argued that the concept is relevant to study forms of social relation between corporations and indigenous societies. Publication about that is little. Indigenous societies across Indonesia insist that they have rights over agrarian sources within their customary territory and the rights are recognized by the Indonesian state as well as international bodies. Academicians only pay attention to the governmentâs responsibility to recognize and respect the indigenous societyâs rights. It is contended that from the concept of CSR a corporation is responsible for recognizing and respecting indigenous societiesâ rights over agrarian sources, but this article demonstrates that realization of indigenous communityâs rights by corporations is dependent upon pressure from indigenous communities rather than coporationsâ initiative.